Altitude development of postmidnight F region field-aligned irregularities observed using Equatorial Atmosphere Radar in Indonesia - Dao, Tam; Otsuka, Yuichi; Shiokawa, Kazuo; Tulasiram, S.; Yamamoto, Mamoru (My University, 2015)
For the first time, vertical rise velocities of postmidnight field-aligned irregularities (FAIs) at low geomagnetic latitudes have been examined near the June solstice by using two-dimensional maps of F region FAI echoes observed with the Equatorial Atmosphere Radar in Indonesia for 3 years starting in May 2010. We found 15 freshly growing FAIs at postmidnight between May and August during the 3 years. The rise velocities of FAIs are smaller at postmidnight than at postsunset, and most postmidnight FAIs do not exceed an altitude of 450 km. Based on the rise velocities, a lower limit for the creation time of the postmidnight FAIs is estimated to be between 21:30 LT and 02:00 LT for 14 of the 15 events, indicating that this class of FAIs is distinct from the postsunset FAIs.
Keywords: Field aligned irregularities; Equatorial atmosphere radar; Indonesia; F region irregularities